Virtual deep seismic sounding method and its applications - Minghui Zhang; Tao Xu; Xiaobo Tian; Guobin Tang; Zhen Liu; Zhiming Bai (地球与行星物理论评)
The SsPmp seismic phase is a seismic phase in which the downward P-wave excited by the far-field direct S-wave is reflected on the Moho surface. It has the advantages of high signal energy, high signal-to-noise ratio, and is not easily affected by the disturbance of near surface sedimentary layers and small-scale crustal structures. Virtual deep seismic sounding method (VDSS) is a detection method developed in recent years that uses the arrival time difference between SsPmp seismic phase and direct Ss wave seismic phase to study crustal thickness (or Moho depth). This article introduces the principles, advantages, and practical applications of the VDSS method. Research has shown that the VDSS method has significant advantages in improving detection accuracy, reducing costs, and environmental impact, and has been successfully applied in different geological environments such as the craton, orogenic belts and sedimentary basins, and the Emeishan large igneous province. It has shown great potential and application value in crustal structure detection. However, the accuracy of the VDSS method is highly dependent on the quality of seismic data, especially the clarity of far-field S-waves and the range of epicenter distance, which greatly limits the appliation of this method in areas with complex geological structures. In the future, the combination of VDSS with traditional receiver function methods, seismic tomography, gravity measurements, and other geophysical methods is expected to provide more comprehensive constraints for crustal structure exploration.